The science of meaning : essays on the metatheory of natural language semantics - Ball, Derek; Rabern, Brian (Oxford University Press, 2020)
With language we command, assert, query, emote, insult, and inspire. Language has meaning, and semantics is the science of linguistic meaning. But what exactly is "meaning"? What is the exact target of semantic theory? This volume explores these questions, in the light of the current state of the art in natural language semantics.